ANALISA KUALITAS HIDUP PENDERITA HIPERTENSI YANG MENGGUNAKAN TERAPI KOMPLEMENTER - Rahma Rahma; Ari Pristiana Dewi; Sri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Hypertension is a silent killer with the highest death rate for cardiovascular disease in the world. Hypertension has affect to human life quality. This study aims to determine the analysis of the quality of life of hypertensive patients using complementary therapies acupuncture in the working area of Harapan Raya Health Center, Bukit Raya District, Kelurahan Tangkerang Selatan, Pekanbaru. This research uses descriptive design. This study was conducted at 88 respondents using a cluster sampling technique. The measuring instrument used is the WHOQOL-BREF questionnaire which is a questionnaire to measure quality of life that has been tested for validity and reliability. Data analysis used is univariate analysis to see frequency distribution. The results showed that the quality of life using acupunture was good (59,1%). This study recommends to the community especially those who have family members to pay more attention to healthy lifestyles to avoid further complications of hypertension. Keywords: Hypertension, Quality of Life, Therapies of complementary.